Investigating the determinants of experts' tax aggressiveness: Experience and personality traits - Kay Blaufus; Tim Zinowsky (Arbeitskreis Quantitative Steuerlehre (arqus), 2013)
This study analyzes how the Big Five personality traits and professional experience affect the aggressiveness of tax preparers' recommendations. To this aim, we conduct a survey among tax professionals of a Big Four accounting firm and tax students. Using treatment-effects regressions, we find that personality traits have direct and indirect effects on tax aggressiveness. The indirect effects are due to a selection effect. Personality traits affect the decision to remain in the organizational environment of the Big Four accounting firm, and the experience in this firm is significantly related to tax aggressiveness. Our data suggest that enhancing work experience at the accounting firm leads to lower tax aggressiveness and that the organizational culture appears to be an important determinant of tax aggressiveness. Moreover, we provide evidence that the danger of potential reputation losses reduces subjects' tax aggressiveness regardless of whether the subject is highly experienced.
Keywords: M40; M41; H25; H26; 330; tax preparers; tax aggressiveness; experience; personality traits; Big Five; reputation loss